Exploring Adult Patients' Perceptions and Experiences of Telemedicine Consultations in Primary Care: A Qualitative Systematic Review - Jack Allen (University Library System, University of Pittsburgh, 2022)
The COVID-19 pandemic transformed a gradual uptake of telemedicine, into a sudden worldwide implementation of telemedicine consultations. Primary care is a particular area affected and one where telemedicine consultations are expected to be the future. However, for effective long-term implementation it is vital that patient perceptions and experiences are understood. The aim of this qualitative systematic review was to explore the perceptions and experiences of adults who have used telemedicine consultations in primary care. Studies were identified through a search of four electronic databases (MEDLINE, EMBASE, CINAHL, and CENTRAL) alongside reference list and citation searches. Quality assessment was conducted using the CASP checklist and data was synthesized using a simplified approach to thematic analysis. From 2492 identified records, ten studies met the eligibility criteria all of which were judged as either good or moderate quality. Three themes were identified which were potential benefits, potential barriers, and beneficial prerequisites for telemedicine consultations in primary care. Within these themes, sixteen sub-themes were identified with examples including accessibility and convenience for potential benefits, lack of face-to-face interaction and impersonal consultations for potential barriers, and continuity of care for beneficial prerequisites. Analysing these subthemes, four main recommendations for practice can be made which are to utilise continuity of care, offer both video and telephone consultations, provide adequate support, and that healthcare professionals should demonstrate an explicit understanding of the patient's health issues. Further research is needed to explore and expand on this topic area and future research should be viewed as a continuous process.